GEOTECHNICAL STUDY FOR ANALYZING SLOPE STABILITY BETWEEN TWO MINING PIT BOUNDARY - Zulfahmi Zulfahmi (Puslitbang tekMIRA, 2022)
This paper is a new concept to increase the safety and mining conservation on PT-X and PT-Y with no boundary gap between the two areas. To optimize coal recovery as a basis of supporting conservation, the two companies needed to adjust coal production in terms of avoiding technical problems at the mining time process due to the rock structure and coal seam at the border were the same. PT-X plans to produce 2 million tons of coal, but the government only approved 1 million tons, while PT-Y still approved 2 million tons. This paper discusses the instability of mining in border locations due to the differences of coal production. The applied methodology is conducting geotechnical modeling by considering statistical aspects of data distribution and the probability of failure. Based on the results of geotechnical modeling by numerical methods on the basis of 2D and 3D for the difference in the production level of 1 million tons in all cross-sections, the FK value is 0.992 - 1.248 with a probability of failure (PI) of 5.40 - 48.00%. Results of modeling analysis show that both single and overall slopes are at a critical level and are not safe. If this difference is narrowed by increasing PT-X's coal production by 1.5 million tons, the border location's mining conditions will stabilize. Therefore, it is necessary to propose to the government for PT-X's coal production to be added by at least 500.000 tons so that the production process of each company runs safely.